PENGARUH LATIHAN HOROZNTAL SWING TERHADAP POWER OTOT LENGAN DAN BAHU PADA ATLET TENIS LAPANGAN PPLP PUTRA RIAU PEKANBARU - Afni, Muwinda; Zainur, Zainur; Juita, Ardiah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The purpose of this research was conducted to find out if there is theeffect of horizontal swing exercise towards shoulder and arm muscle power on athletespplp riau pekanbaru. Type of research used is experiment and using one preetestposttestdesign. Population is research in athletes tennis pplp riau pekanbaru is theentire populations of 6 people. While the sample technique used is total sampling(saturated sample) where all the population is sampled. The sample in this amounted to6 people of athletes tennis pplp riau pekanbaru. The instrument used two-hand medicineball. After that, the data is processed with statistics, normality test with lilifors test atsignificance level ɑ (0.05). The hypothesis is The Effect Of Horizontal Swing ExerciseToward Shoulder And Arm Muscle Power In Mens’s Tennis Athlete Pplp RiauPekanbaru. Based on the analysis of statistical data, there are an average pree-test315,16 and an average post-test 368,33, then the data is normal with an increase of50,17 . Based on t test analysis produces t hitung = 10.26 > t tabel = 1.943. Meaning t hitung> t tabel. Thus, there is the effect of horizontal swing exercise towards shoulder and armmuscle power in men’s tennis pplp riau pekanbaru.Keywords: Horizontal Swing, Shoulder And Arm Muscle Power ,Tennis